O processo civil brasileiro como veículo de concretização e juridicização de normas globais ("Global law") - Barbosa, Luiza Nogueira (2017)
Globalisation has included private and hybrid actors in the world community, whose activities within certain specialized networks result in the production of norms, regulations and standards, which coordinate and govern the behavioural, negotiation and legal interactions of various sectors at the global level without the usual sovereign-territorial barriers of state rights. Despite the – still unresolved – debate about the nature of such global norms, they produce notorious practical effects and are capable of regulating private sectors, functioning as quasi or semi-autonomous legal regimes. This effect on the global sphere results in the infiltration of those rules into the spheres and application territories of national legal systems. The purpose of this study is to investigate the problem of how the Brazilian civil procedure constitutes an instrument, or means, for the introduction, concretization and juridicization of such global norms. In this sense, the first part of the research describes the emergence of non-state actors in the global community, clarifying that understanding the study of these UNOs as part of a Global Law presupposes the rupture of the monist-statecentric paradigm. In this opportunity, the theories of the Fragmentation of Public International Law and that of Global Legal Pluralism are presented, weaving the criticism regarding the scientific insufficiency of such to support with robustness the existence of a supposed Global Law. The next chapter seeks to demonstrate the concrete effects of UNO's in the global community, with case analysis of the new lex mercatoria and lex sportiva. Finally, the third chapter presents the means in which global normative objects are internalized in the legal order of the country, pointing out four possible hypotheses, within: a) civil proceedings with estraneity elements and choice of law by the parties; b) recognition of a foreign judgment that acknowledges the legal nature of non-state norms; c) arbitration award that has elected such rules as applicable law; d) use of these normative objects as ratio decidendi of Brazilian state jurisdiction’s awards. After deepening the matter, the study points out that the concretization and juridicization of UNO's in Brazilian jurisdiction through the civil procedural system occurs in the case of hypotheses "c" and "d", becoming thus concrete legal rules.